From Women's Suffrage to Gender Equity in Costa Rica - Vargas Cubero, Ana Lorena (2025)
The study scope is to analyze the incursion of women in the First Republic Power in Costa Rica from 1949 to 2022, from a gender perspective. This is a descriptive research, under the qualitative analysis approach, establishing from a gender approachas an epistemological framework. Data collection was documentary. It is concluded that the struggles against political discrimination have led to changes in legislation and greater participation and representation of women in elected positions such as deputies, but the road is not yet complete.